Defect Signal Analysis For Nondestructive Testing Assesment - Damhuji, Rifai; Abdalla, Ahmed N.; Kharudin, Ali (Asian Research Publishing Network (ARPN), 2016)
For fast assessment of defects in conductive materials, Eddy current testing is a most widely non-destructive testing (NDT) evaluation methods utilized in industry, especially in oil and gas, aircraft, nuclear and coating industries. Experimental studies of eddy current testing have emerged as an important approach alongside numerical modelling. This paper focus on investigating the defect signal characteristics of carbon steel pipe weld coating inspection using different frequency eddy current testing. The optimum frequency of carbon steel pipe weld coating is verified. Tests have been conducted utilizing positive and negative scanning method with frequency between 10 kHz to 100 kHz. Artificial defect use of this test is the horizontal affected zone (HAZ), centre line and transverse crack. Experimental results showed the frequency can be impression to the amplitude and phase angle eddy current testing signal. The optimum frequency for carbon steel weld plate is 100 kHz.